Capital structure of foreign affiliates and the investment decision: two questions to consider - Merino, Fernando (Journal of Business Economics and Management, 2013)
This paper analyses the ownership structure of foreign affiliates of Spanish firms. In contrast to previous studies on the participation degree, the paper highlights the importance of the previous decision to invest abroad. To do so, an econometric model with a limited dependent variable helps to show that to ignore the previous decision modifies the conclusions of the empirical analyses that raise an empirical model over a sample of firms with foreign affiliates. Additionally, the paper analyses in detail the importance of the cultural and political-legal differences between home and host countries that justify a different type of participation in equity of foreign affiliates. A clear implication for future research in this field is the need to reconsider the econometric approach to include the investment decision. As the paper has shown, a double-hurdle model provides notably different results than the usual approaches, which in this case are closer to the theoretical literature insights. First published online: 08 Feb 2013